Recovery of complete left bundle branch block following heart failure improvement by left bundle branch pacing in a patient. (3rd July 2019) - Li, Yuqiu; Chen, Keping; Dai, Yan; Li, Chao; Sun, Qi; Chen, Ruohan; Yan, Lirong; Lin, Jinxuan; Zhang, Shu
Abstract: A 57‐year‐old male presented with symptomatic systolic heart failure and complete left bundle branch block (LBBB). Left bundle branch pacing corrected LBBB at a low capture threshold (0.5V @0.4ms) with right bundle branch conduction delay and paced QRS morphology changed to near‐normal by adjusting AV delay with diminished RBBD. At 1‐year follow‐up, the patient had a significant improvement in heart failure and LBBB automatically resolved with a rate‐dependent pattern. LBBP may be an alternative to conventional cardiac resynchronization therapy with the likelihood of recovery of LBBB. More research is needed to evaluate the potential use of this pacing strategy in patients with LBBB and heart failure.